AGROCHEMICAL MAPPING OF SOILS AND RATIONAL USE OF FERTILIZERS IN THE AR-ID STEPPE OF NORTHERN KAZAKHSTAN - Shilov Mikhail Pavlovich; Mukanov Miras Kuandykovich; Tokkuzhina Nurgul Saparzhanovna; Zholaushibayeva Diana Azamatovna; Geiko Yuliya Gennadievna (European Research Materials, 2023)
The results of an agrochemical examination of soils make it possible to assess the provision of zonal southern chernozems with basic nutritional elements, which allows the farm to use economically justified doses of mineral fertilizers to obtain the planned crop yield. Agrochemical cartograms contribute to a more rational use of fertilizers in each field, taking into account its order in the crop rotation, soil cultivation technology and predecessor, as well as purposefully bringing the content of nutrients in the soil to the optimal level.